2009
DOI: 10.15560/5.3.542
|View full text |Cite
|
Sign up to set email alerts
|

Angiosperms, tree species in tropical forests of southern Eastern Ghats, Tamil Nadu, India

Abstract: We provide a list of tree species enumerated from a total of 60 ha area sampled in the tropical forests of southern Eastern Ghats, Tamil Nadu, India. A total of 272 tree species (Ā 30 cm girth at breast height) representing 181 genera and 62 families were recorded. Euphorbiaceae with 25 species was the most speciose family, followed by Moraceae (17 species), Rubiaceae (17), Rutaceae (14) and Lauraceae (12). At the generic level, Ficus dominated with 12 species, followed by Diospyros (9), Acacia (6), Terminalia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…Of these, 6 that were assigned evergreen by us were characterized brevideciduous in the earlier study. However, Haldina cordifolia, observed to be deciduous in the present study was marked as evergreen by Pragasan and Parthasarathy (2009);Newton (1988) in central Indian highlands, Mishra et al (2006) in Similipal biosphere reserve, Orissa and Desai and Patel (2010) in Satlasana range forest, north Gujarat observed H. cordifolia as deciduous. Likewise, in Ficus drupacea, leaf flushing was observed from January to midMay in one season whereas the same was observed during September to December in the next season in the same site in Coorg of Western Ghats (Patel, 1997) and the same species has been marked as brevi-deciduous by Pragasan Table 4.…”
Section: Resultscontrasting
confidence: 40%
See 4 more Smart Citations
“…Of these, 6 that were assigned evergreen by us were characterized brevideciduous in the earlier study. However, Haldina cordifolia, observed to be deciduous in the present study was marked as evergreen by Pragasan and Parthasarathy (2009);Newton (1988) in central Indian highlands, Mishra et al (2006) in Similipal biosphere reserve, Orissa and Desai and Patel (2010) in Satlasana range forest, north Gujarat observed H. cordifolia as deciduous. Likewise, in Ficus drupacea, leaf flushing was observed from January to midMay in one season whereas the same was observed during September to December in the next season in the same site in Coorg of Western Ghats (Patel, 1997) and the same species has been marked as brevi-deciduous by Pragasan Table 4.…”
Section: Resultscontrasting
confidence: 40%
“…The degree of gradient of deciduousness is ascertained only by finer field observations . Not surprisingly, we found that our study assigned a different phenology to 15 species (Table 4) in comparison with Pragasan and Parthasarathy (2009). Of these, 6 that were assigned evergreen by us were characterized brevideciduous in the earlier study.…”
Section: Resultsmentioning
confidence: 44%
See 3 more Smart Citations